Abiotic Factors Promote Cell Penetrating Peptide Permeability in Enterobacteriaceae Models - Toyohara, Daichi; Yokoi, Yasuhito; Inoue, Go; Muraoka, Takahiro; Mori, Tetsushi (Frontiers in Microbiology, 2019)
Conventionally, the delivery of biomolecules into bacteria for the generation of characterized or functional mutants have relied greatly on horizontal gene transfer techniques. However, the low compatibility of these techniques with novel or hard-to-transform bacteria currently serves as a challenge to the bioengineering field. Here, we explored the use of cell penetrating peptides (CPPs) as an alternative biomolecule delivery approach by investigating the effects of the abiotic factors during CPP permeation. Using the (KFF)3K-FAM conjugate and Escherichia coli as models, we evaluated four abiotic factors where two of these factors, temperature and solution tonicity promoted (KFF)3K-FAM permeation efficiency. Our data show that optimal (KFF)3K-FAM permeation efficiency was achieved for E. coli at approximately 98.1% under conditions of 37°C (growth optimal temperature) and 50% PBS concentration. Based on these conditions, we subsequently tested the applicability of CPP permeation in various bacterial strains by treating 10 bacterial strains from the Enterobacteriaceae family among which 7 strains have no CPP permeation records with (KFF)3K-FAM. Interestingly, when compared with non-optimized conditions, all 10 strains showed a marked increase in CPP permeation ranging between 20 - 90% efficiency. Although using strains within Enterobacteriaceae that are phylogenetically close, our results hinted on the possibility that with proper optimized of the abiotic factors, CPPs could be compatible with a broad range of bacterial strains. Our efforts suggest that CPP could serve as an effective alternative approach for mutant generation and for biomolecule delivery into novel or hard-to-transform bacteria.